Efektifitas Ukuran Panjang Lubang Masuk Perangkap Tikus Sawah (Rattus argentiventer) - Rifani, Muhammad Indar; Pramudi, Muhammad Indar; Marsuni, Yusriadi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Damage to rice plants due to rice rats (R. argentiventer) starts from the seedbed, controlling rats using traps is a control method that is relatively safer than using chemicals. The aim of this research is to determine the effectiveness of the length of the mouse trap entrance pipe in trapping field mice. This research used a descriptive method to determine the effect of the effectiveness of the length of the trap entrance hole in trapping field mice, consisting of 5 treatments. The results of this research show that mouse traps with an entrance hole length of 15 cm are more effective in trapping field mice compared to traps with entry holes of 20 cm and 25 cm, because traps with an entry hole length of 15 cm are able to trap 3 field mice. Meanwhile, in the control trap, 1 fish was obtained.